Prevalence and Epidemiologic Characteristics of Acute Cystitis, Acute Pyelonephritis and Urinary Tract Infection: Population-Based Analysis Using Health Insurance Review and Assessment Service Bigdata From 2010 to 2024 - Don Hee Lyu; Jae Chul Lee; Chang Hee Han; Sangrak Bae (Urogenital Tract Infection, 2026)
Purpose: This study aims to investigate the long-term prevalence trends and epidemiological characteristics of acute pyelonephritis (APN), acute cystitis (AC), and other urinary tract infections (UTIs) in South Korea using nationwide big data.Materials and Methods: Data for ICD-10 (International Classification of Diseases, Tenth Revision) codes N10.0 (APN), N30.0 (AC), and N39.0 (UTI) were extracted from the Health Insurance Review and Assessment Service database from 2010 to 2024. Annual prevalence per 100,000 persons, sex and age-specific distribution, regional variations, and hospitalization/outpatient patterns were analyzed.Results: The average annual prevalence per 100,000 was 344.4 for APN, 2,250.2 for AC, and 619.1 for UTI. AC reached its highest prevalence in 2024, despite a temporary decline in 2020. All conditions were more prevalent in females, with AC showing the highest male-to-female ratio of 1:20.4. A sharp 3.06-fold increase in APN prevalence was observed in females transitioning from ages 15–19 to 20–24 age group. Conversely, males showed a significant prevalence jump (1.43-fold) after age 80. In regional analysis, Gangwon State (469.5) and Jeju Special Self-Governing Province (177.9) recorded the highest and lowest APN prevalence, respectively. UTI required the longest hospitalization, while APN stays averaged 9.2 days for males and 9.0 days for females. An increase in related healthcare costs was also identified.Conclusions: Age and sex are critical determinants of UTI epidemiology. The distinct spike in young females suggests a link to sexual activity, while the surge in elderly males likely correlates with prostatic conditions. These findings provide essential data for establishing targeted public health policies and clinical guidelines.